Buhay mascot mga babae ng Santiago - Aguilar, Mila.; Lee, Ricardo; Institute for Filipino Cinema; Asia Visions Media Foundation ([Quezon City] The Institute, 1989)
The first episode is a 15 minutes show of commercial mascots, their use and manufacture and the people who operate them. The second episode is a 15 minutes portrait of 1992 presidential candidate Senator Joseph Estrada, including his presidential plans. The last is a 20 minutes show of the women of Santiago, Isabela who have married Japanese farmers for a fee.
Buhay mascot (15 min.) -- Erap (15 min.) -- Hanayome San : mga babae ng Santiago (20 min.)
VHS
Host, Rowena Moran.
Keywords: Estrada, Joseph; Mascots; Intermarriage; Sociology